Credibility of online reviews and initial trust: The roles of reviewer's identity and review valence - Kusumasondjaja, Sony; Shanka, Tekle; Marchegiani, Christopher (Sage Publications, 2012)
This article investigates the main and interactional effects of review valence and the presence of source identity on consumer perception of credibility of an online review and initial trust of travel services being reviewed. An experimental design is developed involving 639 travel consumers. Results indicate that a negative online review is deemed more credible than a positive online review, while a positive online review leads to a greater initial trust than a negative review. These findings apply when the identity of the reviewer is disclosed. However, when the reviewer’s identity is not disclosed, there is no significant difference between positive and negative reviews either in terms of perceived credibility or impact on consumer trust. Theoretical and managerial implications, limitations and future directions are also discussed.